SYNTHETIC POTENTIAL OF 9,10-ANTHRAQUINONYLDIAZONIUM SALTS - Stasevich, Maryna; Zvarych, Viktor; Novikov, Volodymyr; Vovk, Mykhailo (Ukrainian Chemistry Journal, 2020)
For the first time, the literature sources concerning the chemical transformations of diazonium salts of 1(2)-amino-9,10-anthracenediones are generalized and systematized. The potential of 9,10-dioxoanthracenyldiazonium salts as key substrates in the preparation of various linear-functionalized, acyclic and heterocyclic derivatives has been determined. The main synthetic transformations of diazonium salts of amino-9,10-anthracenediones, which are  realized without preserving the azo function lead to the formation of reaction products of Sandmeyer, Meerwein, and Gomberg–Bachmann–Hay, are analyzed. The use of 9,10-dioxoanthracenyldiazonium salts or products of their transformations for obtaining heteryl-containing condensed and functionalized derivatives is presented.